Pengaruh Model Pembelajaran Problem Based Learning Terhadap Peningkatan Kemampuan Literasi Matematis Siswa SMP - Miska, Luthfiyyah; Zulkifli (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
ABSTRACT: Aim to examine the effect of the implementation of the Problem-Based Learning (PBL) model on junior high school students' mathematical literacy skills. The research employed a quasi-experimental method using a Control Group Pretest-Posttest design. The study was conducted at MTs Mon Malem, Aceh Besar, with samples consisting of Class VIII-1 and Class VIII-2, each comprising 15 students, selected through Simple Random Sampling. The data collection instruments were the mathematical literacy pretest and posttest sheets, each consisting of two essay questions. The collected data were analyzed using an Independent Samplei T-test at a significance level of 0,05 and normalized gain (N-Gain) analysis to measure the improvement in students mathematical literacy skills. The result indicated that there was an improvement in students' mathematical literacy skills after the implementation of the Problem-Based Learning model. A significance value of p < 0,05 from the hypothesis testing showed that the improvement was statistically significant. Therefore, the Problem-based Learning model is effective in improving students' mathematical literacy skills.